Permselective Membranes for Gas Processing Replacing the Conventional Methods - K. C. Khulbe; T. Matsuura; C. Y. Feng (Journal of Chemical Engineering Research Updates, 2016)
Membrane technology has gained acceptance for gas separation and recovery as membranes are friendly to the environment and less expensive. Membranes are starting to play a great role in industries such as separation and production of gases, sweetening of natural gas, processing of biogas and syngas, and oil refineries. This article evaluates the replacement of the conventional methods for gas processing by perm selective membranes and also offers an overview of the membrane technology in current use for gas processing in industries.